Characterization of the Florida Fresh Fruit and Vegetable Industry Using Hydroponic Systems or Protected Agriculture Structures - Robert C. Hochmuth; Dilcia E. Toro (EDIS)
UF/IFAS Extension faculty, allied industry representatives, and growers determined the need to assess the size and scope of the protected agriculture industry in 2013 by surveying growers in Florida. The primary focus was to document the types of protected agriculture structures, crops, and growing systems being used. In addition, secondary information on location of operations, pest concerns, expected expansion, etc. was collected on many operations. The results documented a significant expansion of the industry in terms of both size and scope. This 8-page fact sheet was written by Robert C. Hochmuth and Dilcia E. Toro, and published by the UF Department of Horticultural Sciences, August 2014.